Comparative performance analysis and material exploration of ECO-friendly highly efficient perovskite solar cells. (27th September 2022) - Anik, M Hussayeen Khan; Mahmud, Sakib; Islam, Mohammad Atiqul; Talukder, Hriteshwar; Biswas, Shovasis Kumar; Islam, Sharnali
Abstract: Recent development of perovskite solar cells (PSCs) is directed toward the search for lead-free material with superior efficiency, owing to the intoxication and stability issues associated with the lead-based PSCs. Despite the efforts, plenty of exploration is still required to attain the optimum material for perovskite, along with the electron transport layer (ETL), and hole transport layer (HTL). In this study, two less explored perovskite materials Cesium Tin Germanium Halide (CsSnGeI3 ) and Cesium Copper Antimony Chloride nanocrystals are compared to their Pb-based counterpart of Methylammonium Lead Iodide (MAPbI3 ). Thorough numerical investigations and comparative evaluation of these three material-based PSCs were done using a solar cell capacitance simulator (SCAPS-1D). Based on the suitable band alignment with the absorber layers, three selected distinct ETL (TiO2, ZnO, PCBM) and HTL (Cu2 O, CZTSe, CuSCN) materials demonstrated excellent compatibility. The effect of back metal contact, temperature, series, and shunt resistance on the photovoltaic parameters was also elucidated for all three perovskite materials. Increasing the work function of back contact up to 5.9 eV improves the photovoltaic parameters, indicating selenium to be an optimum material. Numerical analysis of 27 attainable structures yields the best one to be CZTSe/CsSnGeI3 /PCBM with a power conversion efficiency of 32.41% ( J S C = 28.73 mA cm −2, V O C = 1.29 V, and FF = 87.35%). The PCE obtained from these structures ranges from 25.14% to 32.41%, indicating that all the reported structures here have the potential to be highly efficient, lead-free, and stable solar cell structures.